Challenges faced by Petronas Penapisan Melaka Sdn Bhd in conducting capability management trainings / Siti Soraya Abd. Razak - Abd. Razak, Siti Soraya (2012)
This study identifies the “Challenges Faced By PETRONAS PENAPISAN MELAKA SDN BHD, (PP(M)SB) In Having Capability Management Trainings” which can improve staffs’ ability in producing productivity staffs. Besides that, it will be proven by types of training provided by PP(M)SB in order to support this study. The trainings are very essential to PP(M)SB because PP(M)SB has been known as ‘The Best Refinery In Asia Pacific’. In order to conduct this study, the researcher uses both sources of data which are primary data and secondary data. Through this study the researcher has identified three main challenges faced by PP(M)SB when conducting Capability Management trainings which are employees’ interest, technology capabilities and also strategic Human Resource Management.